2021
DOI: 10.3138/jmvfh-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of family acceptance into the military community among U.S. LGBT service members: A mixed-methods study

Abstract: Lay Summary There are approximately 16,000 families of lesbian, gay, bisexual, or transgender (LGBT) service members in the U.S. military, but very little is known about how accepted they feel in the communities in which they live. This study begins to address this question by considering the perspectives of LGBT service members, which they shared both in response to an online survey and in interviews. Findings suggest that many service members believe their spouses and families are accepted by their chain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…55 Studies on improving inclusion of historically marginalized populations in the workplace have also recommended developing and consistently adhering to an anti-discrimination policy, creating official support and community-building programs for targeted groups, encouraging vocal allyship by modelling it at the highest levels of the organization and among high-status individuals, such as medical doctors and chaplains, and offering LGBT-friendly benefits in areas such as assistive reproductive technology, gender-affirming medical care, and access to pre-exposure prophylaxis when indicated for those at heightened risk of being infected with HIV. [56][57][58] Future research on this topic should examine differences in career intent by military career field, mental and physical health status, sexual orientation and gender identity sub-groups, and family needs. Moreover, the current study found that non-White SMs were at twice the risk for indecision about their military career plans compared with White SMs; research on the causes of this disparity should be conducted, and findings could suggest broader issues of inclusion across minority groups in the U.S. Armed Forces.…”
Section: Discussionmentioning
confidence: 99%
“…55 Studies on improving inclusion of historically marginalized populations in the workplace have also recommended developing and consistently adhering to an anti-discrimination policy, creating official support and community-building programs for targeted groups, encouraging vocal allyship by modelling it at the highest levels of the organization and among high-status individuals, such as medical doctors and chaplains, and offering LGBT-friendly benefits in areas such as assistive reproductive technology, gender-affirming medical care, and access to pre-exposure prophylaxis when indicated for those at heightened risk of being infected with HIV. [56][57][58] Future research on this topic should examine differences in career intent by military career field, mental and physical health status, sexual orientation and gender identity sub-groups, and family needs. Moreover, the current study found that non-White SMs were at twice the risk for indecision about their military career plans compared with White SMs; research on the causes of this disparity should be conducted, and findings could suggest broader issues of inclusion across minority groups in the U.S. Armed Forces.…”
Section: Discussionmentioning
confidence: 99%
“…Military families are commonly seen as a single large entity, when in reality they are diverse (Cozza et al, 2005; Totenhagen & Albright, 2018). Such diversity includes LGBT (lesbian, gay, bisexual, and transgender) servicemembers and families, who feel accepted within the overall military family community while also feeling a lack of acceptance from base or military offered programs (Sullivan et al, 2021). It is also important to note that 6.8% of married servicemembers are in a dual-service marriage, presenting additional nuances to the military family structure (DoD, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%